Quantification of Organophosphate and Carbamate Pesticide Residues in Maize - Ogah C.O. and Coker H.B. (Journal of Applied Pharmaceutical Science)
Use of pesticides in agriculture to protect crops against destructive pests often leads to residues of these chemicals in foods. The levels of pesticide residues in food are often determined as a means of assessing appropriate use as well as the potential for human exposure to these chemicals and hence their potential damage to human health. The aim of this study was to determine the concentration of organophosphate and carbamate pesticides in maize samples collected from various markets in Lagos State and compare these values with established safety values. Maize (Zea mays L.) samples purchased from different markets in LagosState were analyzed for residues of organophosphate and carbamate pesticides. Analysis was done using gas chromatograph with mass spectrometric detector (GC-MS) after careful extraction and cleanup. It was found that all the maize samples contained residues of one or more organophosphate or carbamate pesticides. Mean concentrations ranged from 12.0 to 1565.4 µg/kg. Maximum residue limits (MRL) of some of the pesticides were exceeded in up to 10% of samples.
Keywords: Pesticide residue, Maize, Organophosphate, Carbamate Lagos.